ANTINOCICEPTIVE PROPERTIES OF LEAF AQUEOUS EXTRACT OF CROSSOPTERYX FEBRIFUGA (AFZEL. EX G. DON) BENTH (FUDMA JOURNAL OF SCIENCES, 2022)
Nociceptive pain is a sensational discomfort that is usually associated with injury or illness found affecting the body either internally or externally. Crossopteryx febrifuga is one of the medicinal plants which are locally used in the management of pain especially in the North Central Region of Nigeria. Many conventional drugs which are being applied in managing pain aside being not affordable and readily accessible by the majority of people at rural areas have one side effect or the other. Therefore, this research was conducted to evaluate the potentiality of aqueous extract of C. febrifuga in alleviating pain in Wistar rats. The study was carried out using acetic acid induced writhing and Edson hot plate methods. On acetic acid induced pain, the aqueous extract at 50 and 100 mg/kg inhibited pain significantly by reducing the number of writhing by average of 3.9 per minute while at 200 mg/kg, the extract reduced pain by reducing the number of writhing by average of 4.2 per minute. Similarly, the extract at all doses administered in hot plate induced method inhibited pain by increasing the time the rats took to jump off the hot plate. The data obtained from the analgesic study of C. febrifuga aqueous extract suggests that it has anti-nociceptive property as evident in both models. This, therefore revealed that the plant leaf aqueous extract possessed both the peripherally and centrally mediated analgesic properties. For this reason, the plant leaf could be a potential antinociceptive agent if subjected to clinical trial and proved
Keywords: Antinocicepyive; Crossopteryx febrifuga; Evaluation; Pain; Writhing